Controle químico e a influência da palha de cana-de-açúcar e da profundidade de semeadura na emergência de plantas daninhas - Silva, Paulo Vinicius da (Universidade Federal de São Carlos, 2013)
The implementation of the mechanized system of the sugar cane has lead a number of direct and indirect benefits to the sugar cane culminating changes in the productive system, among them, changing the infesting flora and the herbicide dynamic. On account of that, this present paper has as goal to study the emergency aspects and the chemical handling of the weeds species. Merremia aegyptia (L.) Urban (Convolvulaceae); Ipomoea purpurea (L.) Roth (Convolvulaceae); Luffa aegyptiaca Miller (Cucurbitaceae); Mucuna aterrima Piper e Tracy (Fabaceae - Leguminosae) e Ricinus communis (L.) (Euphorbiaceae). It was developed two experiments in the greenhouse of Agricultural Science, Universidade Federal de São Carlos, Araras, SP. The first has studied, isolated, the emergency ability of the weeds in designs entirely randomized in factorial scheme 4 x 5, being analyzed in four amount of straw (0,5,10 and 15t ha), five depths of sowing(0, 2, 4, 8 and 10 cm) with for repetition in soil with clayey texture. The emergency percentage of the plants was evaluated until 21 days after the sowing, when the leaf area was also evaluated (cm2), dry mass (g) and height (cm). The second experiment evaluated after emergency controlling of weeds, through the curves of response with amicarbazone herbicide (1400 g ha-1), saflufenacil (50 g ha-1), mesotrione( 120g ha-1) and sulfentrazone(600g ha-1). The herbicides were administered when the weeds presented until the second pair of real leaves, in doses 1,5 D; 1,0 D; 0, 5 D, 0,25 D e o 0,00 D, where D means a commercial dose of product. The evaluations were made after 7, 14 and 21 days the application of the treatments (DAS) and the dry mass after 21. In relation to the emergency ability, the species analyzed presented different responses on account of the sowing depth and the amount of straw placed on the soil surface. For the species of L. aegyptiaca, I. purpurea, R. communis the sowing that was more supercial resulted in a higher percentagem of emercengy of seedlings, regarding the placement of M. atterima seeds to the 0 cm it has resulted in a less number of seedlings. The L. aegyptiaca, M. aterrima e I. purpurea species had presentend less leaf area, height and dry mass at t he moment the seeds were placed in a supercial way (0cm). In relation to the herbicides administration after emergency condition of the weeds, it has verified that the application of amicarbazone provided levels of controlling to 80% in all the doses administered except de R. communist showing to be efficient on weeds handling. The saflunefacil wasn t efficient on L.aegyptiaca controlling and the mesotrione wasn´t efficient on controlling levels to 80% in all the species and doses used. On account of that we can conclude the species analyzed presented adaptation to the harvesting system without previous burning emerging up to 10cm and 15 t ha-1straw on the soil. The response given by the plants has showed changes, in relation to the chemical handling was observed that different levels of susceptibility of weeds regarding to the herbicides administered after emergency, being more efficient amicarbazone and sulfentrazone.
Keywords: Agricultura; Cana-de-açucar - cultivo; Mamona; Erva daninha; Herbicidas; Plantas daninhas; Emergência; Cane sugar; Weeds; Emergency; Herbicides; CIENCIAS AGRARIAS